Simplified algebraic estimation technique for sensor count reduction in single-phase converters with an active power buffer - Yuan, Huawei (2022)
Active pulsating power buffering (APPB) is an emerging technology that can effectively minimize the energy storage requirement of single-phase power conversion systems, potentially leading to high density and high reliability design. Nonetheless, the implementation of APPB generally requires the addition of excessive number of sensors in the circuit. Employing many sensors not only increases the system's volume and cost, but also undermines the system's robustness. Existing methods of reducing the sensor count in single-phase converters with an APPB suffer from issues such as high design complexity, noise sensitivity, and/or computational complexity. In this article, a simplified algebraic estimation technique is proposed to tackle the high sensor count problem. The proposed technique is intuitive to design and applicable to different topologies. It can effectively reduce the number of sensors while yielding similar or even better system's performance than that with a full set of sensors. Moreover, the technique features very low computational complexity, and can thus be easily implemented by low-cost microcontrollers. Experiments are conducted to verify the feasibilities of the proposed estimation and sensor reduction method. With this method, the sensor count can be reduced by 50%, while achieving a nearly 20-times computational time reduction as compared to that of the conventional method.